2020
DOI: 10.1155/2020/8867349
|View full text |Cite
|
Sign up to set email alerts
|

Induced Pluripotent Stem Cell-Differentiated Chondrocytes Repair Cartilage Defect in a Rabbit Osteoarthritis Model

Abstract: The aim of this study was to explore the therapeutic effect of iPSC-mesenchymal stem cell (MSC)-derived chondrocytes in a rabbit osteoarthritis (OA) model. The iPSCs were characterized by gene expressions, immunostaining of pluripotent markers, and in vivo teratoma formation. iPSC-differentiated MSCs were characterized by flow cytometry and trilineage differentiation. A rabbit OA model was established by the transection of the anterior cruciate ligament. The therapeutic effect of transplanted iPSC-MSC-chondroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…Some researchers found decreased expressions of inflammatory and catabolic markers including IL-1β, TNF-α, and MMP13, after AT-MSCs injection [ 104 ], BM-MSCs injection [ 105 ], or induced pluripotent stromal cell-chondrocytes transplant in KOA model. However, no difference in Col-II and Col-I expression was found between transplanted cartilage and other groups [ 106 ]. One study determined that both IL-1β and TNF-α immunostaining in chondrocytes in the cartilage were significantly enhanced after human umbilical cord-derived MSCs treatment and reserved almost back to normal tissue.…”
Section: Functions Of Msc-based Therapy For Cartilage Regeneration In Koamentioning
confidence: 99%
“…Some researchers found decreased expressions of inflammatory and catabolic markers including IL-1β, TNF-α, and MMP13, after AT-MSCs injection [ 104 ], BM-MSCs injection [ 105 ], or induced pluripotent stromal cell-chondrocytes transplant in KOA model. However, no difference in Col-II and Col-I expression was found between transplanted cartilage and other groups [ 106 ]. One study determined that both IL-1β and TNF-α immunostaining in chondrocytes in the cartilage were significantly enhanced after human umbilical cord-derived MSCs treatment and reserved almost back to normal tissue.…”
Section: Functions Of Msc-based Therapy For Cartilage Regeneration In Koamentioning
confidence: 99%
“…The gene expression profiles of primary MSCs and iMSCs are very similar, but iMSCs show reduced capacity in suppressing T cell proliferation, suggesting a lower immunomodulatory property [ 27 ]. Nevertheless, age-related DNA methylation that was accumulated during in vitro culture was overall reset in iMSCs [ 29 , 30 ], consistent with a stronger regeneration ability of iMSCs in animal disease models and higher proliferation rates when compared to primary MSCs [ 31 , 32 , 33 , 34 ].…”
Section: Imscs For Regenerative Therapiesmentioning
confidence: 91%
“…A similar observation was noted in the Chang team, which analysed iChondrocytes obtained in comparable conditions in a rabbit model. The researchers demonstrated that the differentiated chondrocytes effectively repaired cartilage defects in vivo and indicated a downregulation of catabolic and proinflammatory cytokines [120]. The possible explanations for this phenomenon were related to the rejuvenation of cells during differentiation and, also, the confirmation of their MSC nature, which is known for its suppressive and protective properties [88].…”
Section: Direct Methods For Obtaining Chondrocytes From Ipscsmentioning
confidence: 99%